ANARCHISM AND PHILOSOPHY - Di Cesare, Donatella (Soft Power, 2025)
The meeting between anarchy and philosophy has been preparing for some time now, for years now through meetings, debates, conferences, miscellanies, but above all individual contributions. First of all, it is a question – as I happened to say in an article published for the Italian journal Aut aut and for the American website Ill Will – of deconstructing anarchism to redeem anarchy. Classical anarchism has fallen into the trap of naively understood power relations. Just think of that very modern way of understanding both the subject and the State which culminates in a Manichaean vision: if the subject were by nature good, and the State bad, it would be enough to overturn the scheme personified by Hobbes’s Leviathan, for which the good State it would redeem the human individual otherwise devoted to being a wolf. This very simplification has not worked – not even in politics.